2017
DOI: 10.1038/s41598-017-07537-6
|View full text |Cite
|
Sign up to set email alerts
|

Tilt-less 3-D electron imaging and reconstruction of complex curvilinear structures

Abstract: The ability to obtain three-dimensional (3-D) information about morphologies of nanostructures elucidates many interesting properties of materials in both physical and biological sciences. Here we demonstrate a novel method in scanning transmission electron microscopy (STEM) that gives a fast and reliable assessment of the 3-D configuration of curvilinear nanostructures, all without needing to tilt the sample through an arc. Using one-dimensional crystalline defects known as dislocations as a prototypical exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…[3] for the slopes of the 2D projections of the intersections between the sample surface and both twin boundaries and (ix) a relation of the ratio between the projection widths of both twin boundaries w 2 =w 3 from Eq. [9]. A solution with c s >0 is chosen to ensure that the reconstructed geometry corresponds to the setup adopted in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[3] for the slopes of the 2D projections of the intersections between the sample surface and both twin boundaries and (ix) a relation of the ratio between the projection widths of both twin boundaries w 2 =w 3 from Eq. [9]. A solution with c s >0 is chosen to ensure that the reconstructed geometry corresponds to the setup adopted in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…If the orientations of the crystal and the sample are known, Eq. [9] can also be used to determine the thickness of the sample.…”
Section: Obtaining the Crystal Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps surprisingly, even these small angular ranges can provide useful information in TEM experiments. One example was shown by Oveisi et al (2017), who performed 3D reconstructions of dislocations using only two beams, separated by 1.56°. This experiment demonstrated that with sufficiently strong prior assumptions (in their case, assuming a 1D curvilinear object), useful 3D information can be obtained from small angular ranges.…”
Section: Mbed 3d Tomographic Reconstructionmentioning
confidence: 99%
“…It only requires a few images. Unfortunately, state-of-the-art methods [8,9,10,11] still involve substantial manual intervention for line detection and matching.…”
Section: Introductionmentioning
confidence: 99%